EDUKASI MENDAPATKAN OBAT BERKUALITAS MELALUI â€œCEK KLIK BPOMâ€ BERDASARKAN PANDUAN DAGUSIBU IKATAN APOTEKER INDONESIA - Fathnin, Fildza Huwaina; Santoso, Arifin (Jurusan Farmasi FMIPA Universitas Tadulako, 2023)
Health indicator from BPS which states the percentage of people who do self-medication is 72.19% in 2020 where this has increased from 69.43% in 2019. Providing information about treatment is one of the responsibilities of pharmacists aimed at improving therapeutic outcomes by maximizing the use of appropriate and quality medicines. Objective: To provide education to obtain quality medicines through â€œCek BPOMâ€ based on the DAGUSIBU guideline of the Indonesian Pharmacists Association. The solution to the problems above is that it is necessary to increase public understanding about education to get quality medicines through